Targeted single-cell gene induction by optimizing the dually regulated CRE/loxP system by a newly defined heat-shock promoter and the steroid hormone in Arabidopsis thaliana - Tomoi, Takumi; Tameshige, Toshiaki; Betsuyaku, Eriko; Hamada, Saki; Sakamoto, Joe; Uchida, Naoyuki; Torii, Keiko U.; Shimizu, Kentaro K.; Tamada, Yosuke; Urawa, Hiroko; Okada, Kiyotaka; Fukuda, Hiroo; et al. (Frontiers in Plant Science, 2023)
Multicellular organisms rely on intercellular communication systems to organize their cellular functions. In studies focusing on intercellular communication, the key experimental techniques include the generation of chimeric tissue using transgenic DNA recombination systems represented by the CRE/loxP system. If an experimental system enables the induction of chimeras at highly targeted cell(s), it will facilitate the reproducibility and precision of experiments. However, multiple technical limitations have made this challenging. The stochastic nature of DNA recombination events, especially, hampers reproducible generation of intended chimeric patterns. Infrared laser-evoked gene operator (IR-LEGO), a microscopic system that irradiates targeted cells using an IR laser, can induce heat shock-mediated expression of transgenes, for example, CRE recombinase gene, in the cells. In this study, we developed a method that induces CRE/loxP recombination in the target cell(s) of plant roots and leaves in a highly specific manner. We combined IR-LEGO, an improved heat-shock-specific promoter, and dexamethasone-dependent regulation of CRE. The optimal IR-laser power and irradiation duration were estimated via exhaustive irradiation trials and subsequent statistical modeling. Under optimized conditions, CRE/loxP recombination was efficiently induced without cellular damage. We also found that the induction efficiency varied among tissue types and cellular sizes. The developed method offers an experimental system to generate a precisely designed chimeric tissue, and thus, will be useful for analyzing intercellular communication at high resolution in roots and leaves.